Object Oriented Finite Element Modelling and Fracture Analysis of Epoxy-Clay Nanocomposite - Jasra, Yogeshwar (My University, 2014)
Nanocomposites contains highly variable and irregular angular structure of fillers. This work describes numerical modelling of epoxy-clay nanocomposites based on the real mapping of nano/microstructures. The fundamental material characterisation was conducted using scanning electron microscopy (SEM). To model exact morphology of epoxy-clay nanocomposite, computational models were established by implementing an innovative object-oriented finite element analysis code (OOF). The mechanical and thermal properties of nanocomposites calculated by OOF was in good agreement with the theoretical models. The propagation of cracks, stress and displacement distribution in epoxy-clay nanocomposite is also studied by Abaqus Extended Finite Element (XFEM).
ME, MED
Keywords: epoxy clay nanocomposites; finite element analysis